Intervention of Screening Programme for Hypertension and Lipid Profile on Prescribing Pattern of Antihypertensive and Antihyperlipidemic Agents: Pharmaceutical Science-Pharmacy practice for good health promotion - Madeshwaran. M; Parimalakrishnan. S; Manivannan. R (International Journal of Life Science and Pharma Research, 2022)
The aim of the present study is to assess the impact of screening programme for the patients visiting community pharmacies and factors influencing the prescribing pattern of antihypertensive and/ or antihyperlipidemic agents. The study was designed as a prospective cohort study conducted between December 2017 and November 2019. Data were collected from the hypertensive patients visiting regularly in the 5 selected community pharmacies located at 5 Taluks of Erode district, Tamil Nadu, India. The required data were collected either from the patient’s record or interview. Data were collected from 946 (75.68%) patients of 1250 patients visited the selected community pharmacies.49.4% and 50.6% of patients were randomly allotted to the control (group I) and intervention (group II) groups respectively.In this study 50.56% and 46.67% of males were in group I and II respectively. Average SBP was measured as 151.5 ± 11.8 mmHg and 168.1 ± 13.6 mmHg for the patients in group I and II respectively whereas 92.9 ± 9.3 mmHg and 92.6 ± 9.5 mmHg were the DBP readings among the patients in group I and II respectively. Average total cholesterol was measured as 253.66 ± 33.67 mg/dL and 271.04 ± 39.91 mg/dL for the patients in group I and II respectively. The difference in the prevalence is 0.7 and 2.05 for the antihypertensive and antihyperlipidemic agents respectively whereas the incidence was observed as 4.75 and 2.5 for the antihypertensive and antihyperlipidemic agents respectively. The odds ratio of SBP and DBP is 1.12 and 0.99 respectively in the group II. The values of multivariate analysis showed that there is an agreement between intervention and utilization pattern of antihypertensive and antihyperlipidemic agents. It is to conclude that the preliminary screening of blood pressure and lipid profile showed many patients were not visiting regularly for consultations. The screening programme has resulted in good improvement in the utilization pattern of antihypertensive and antihyperlipidemic agents. The age, lipid levels and comorbid conditions were main factors among the individuals which have determined the prescribing pattern of agents.